2004
DOI: 10.1002/ajh.20140
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of anemia in the elderly: Cross‐sectional study of three urban Korean population samples

Abstract: We conducted a prospective study to assess the prevalence and clinical characteristics of anemia and to define the risk factors for anemia in older Koreans. From October 2002 to November 2002, 1,254 subjects over the age of 60 years were selected from a crosssectional study. All subjects underwent a complete medical history taking and laboratory testing, which included; a complete blood cell count, reticulocyte, liver and renal function tests, lipid profiles, and iron profiles. The median age was 70 years old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
41
5
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 19 publications
16
41
5
3
Order By: Relevance
“…However, while postmenopausal estrogen levels decrease, there is an increase in red cell mass to levels that are similar to those in males, which makes it unreasonable to use different criteria for anemia in each gender 21,22 . In our study 380(39.92%) were males and 572(60.08%) were females, which was higher than other studies like in the Kaur et al 23 and Nasrin A. Qureshi et al 24 , where there was no statistical difference in both gender, and in contrast to the Chul won choi et al study in which 11.4% were males and 2.1% were females 25 . In our study Microcytic hypochromic anemia 56.05% (male) and 50.35% (female) is the predominant type of anemia as seen in Gerardo et al studies 26 , Nasrin A. Qureshi et al and S Patel et al 27 study in which microcytic hypochromic anemia was seen in 72%.This finding was in contrast to the Kaur et al 23 in which normocytic normochromic anemia is the predominant type, 56%.…”
Section: Discussioncontrasting
confidence: 56%
“…However, while postmenopausal estrogen levels decrease, there is an increase in red cell mass to levels that are similar to those in males, which makes it unreasonable to use different criteria for anemia in each gender 21,22 . In our study 380(39.92%) were males and 572(60.08%) were females, which was higher than other studies like in the Kaur et al 23 and Nasrin A. Qureshi et al 24 , where there was no statistical difference in both gender, and in contrast to the Chul won choi et al study in which 11.4% were males and 2.1% were females 25 . In our study Microcytic hypochromic anemia 56.05% (male) and 50.35% (female) is the predominant type of anemia as seen in Gerardo et al studies 26 , Nasrin A. Qureshi et al and S Patel et al 27 study in which microcytic hypochromic anemia was seen in 72%.This finding was in contrast to the Kaur et al 23 in which normocytic normochromic anemia is the predominant type, 56%.…”
Section: Discussioncontrasting
confidence: 56%
“…[22] For Korean elderly population with median age of 70 years, the prevalence of anemia was 13.6%. [23] These previous reports [4,5,[21][22][23] have not investigated the effect of nutrient intakes, although these differences may be influenced by dietary factors such as dietary iron intake and/or intake of iron supplements. In fact, iron intakes in the current study were much lower compared with those in the US [15].…”
Section: Discussionmentioning
confidence: 99%
“…The most common pattern of anemia in their study has been found to be normocytic anemia amounting to 93.5% and 3.5% of them being microcytic, and 3% were macrocytic anemias. 3,5 In the present study, percentage of anemia in males was 64.74% and in females 70.58%. All the types of anemia based on peripheral smear were evident, normocytic being the commonest constituting 78.86%, followed by microcytic hypochromic 11.11%, macrocytic 5.96% and dimorphic 4.07%.…”
Section: Discussionmentioning
confidence: 79%
“…Choi CW et al in their study of anemia in elderly have observed 171 out of 1254 patients to be anemic. 5 Out of them 144 (11.4%) have been women and 27 (2.1%) men. A significant difference in prevalence of anemia has been found among the age 60-69 years, 70-79 year and 80 and above years.…”
Section: Discussionmentioning
confidence: 99%